The Cost of Debt for REITs: The Mortgage Puzzle. Issue 2 (1st October 2020) - Allen, Linda; Letdin, Mariya
Abstract: Established, low-leverage equity REITs with access to the public debt market rely on both non-recourse mortgages and full recourse bonds/notes as sources of long-term debt. Interest rates on secured, non-recourse debt (mortgages) include a costly strategic default option premium and do not benefit from a firm's overall financial capacity. We find that use of non-recourse, mortgage debt is more likely for longer-term, smaller borrowings, and during recessionary periods, consistent with REITs valuing financial flexibility in their capital structure. The higher rates for property-level debt suggest a benefit to REITs versus single asset investors in terms of cost of capital. Since REITs also access debt at the corporate level, the spread between long-term non-recourse debt and long-term recourse debt implies a benefit to the REIT structure.